Almath Game Berbasis Aktivitas Metakognisi Terhadap Kemampuan Penalaran Matematis Siswa pada Materi Bentuk Aljabar Kelas VII SMP (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to produce learning media in the form of almath games based on metacognition activities on students' mathematical reasoning abilities on algebraic form materials. The research method used is Research and Development (R&D) with the ADDIE development model which includes five stages: analysis, design, development, implementation, and evaluation. The research subjects consisted of grade VII students at SMP Negeri 5 Sungai Kakap with a total of 29 students. The research instruments used included expert validation sheets, teacher and student response questionnaires, and learning outcome tests (posttests). Based on the results of the validation of material experts and media experts with an overall average score of 92.56% with very valid criteria. The results of the practicality score were seen from the teacher response questionnaire and the student response questionnaire with an overall average score of 92.56% with very practical criteria. Meanwhile, the effectiveness value of the developed media was obtained from the results of the students' posttest. For the results of class completion (%) ≥ 75 who obtained a percentage of 89.65% with very effective criteria. Based on the results of the study, the almath game media based on metacognition activities on students' mathematical reasoning skills is suitable for use in mathematics learning, especially in algebraic form material for grade VII junior high school.